台湾男女形象的重构与男同困境——以电影《关于我和鬼变成家人的那件事》为例 = The reconstruction of gender images and predicament of gay men in Taiwan: a case study of “Marry My Dead Body” - 林婉惠 Lin, Wanhui (Nanyang Technological University, 2025)
台湾在2019年正式通过了同性婚姻法案，成为了亚洲首个同性婚姻合法化的国家。这其中不乏台湾同志团体的积极推动和争取。当法律不再是限制在台同志收获爱情和幸福的限制后，在台同志是否就都取得了他们“圆满的结局”了呢？2022年上映的《关于我和鬼变成家人的那件事》以同性婚姻合法化后的台湾社会为背景设定揭露台湾男同性恋伴侣的困境。《关于我和鬼变成家人的那件事》通过诙谐的“直男警察与同志鬼冥婚”设定桥段刻画出不同性别形象，再以调查车祸事件的剧情去再现台湾社会对男同的偏见与接受度，以及男同之间的问题。笔者认为电影所企图展现的同性婚姻合法化后的台湾社会内涵和同志困境值得深究与思考。此外，电影里的男性与女性形象建构随着剧情的发展也有了不同的刻画，因此笔者将探讨电影其中性别形象的转变与意义。本文将以电影《关于我和鬼变成家人的那件事》为文本，通过分析文本探讨电影中所建构的性别形象与意义，再现了台湾男同面临的困境与其原因，以及题材的局限性。In 2019, Taiwan became the first Asian country to legalize same-sex marriage, a milestone largely driven by the efforts of Taiwan's LGBTQ+ community. However, after the legal barriers to love and happiness for same-sex couples were lifted, have Taiwanese LGBTQ+ individuals truly achieved their "happy ending"? The 2022 film “Marry My Dead Body” vividly portrays the challenges faced by Taiwanese gay couples in the post-legalization era. Through the humorous premise of a "gay ghost marriage" between a straight policeman and a deceased gay man, the film explores diverse gender identities and highlights the ongoing prejudice and acceptance struggles faced by gay men in Taiwan. As the film presents an insightful depiction of the invisible struggles and gender identity issues that persist after the legalization of same-sex marriage, it is necessary to further explore and analyse this topic in depth. Additionally, the evolving portrayal of male and female characters throughout the film offers a significant subject for analysis. Therefore, this essay analyses the film “Marry My Dead Body” to examine the construction and transformation of gender identities, the challenges faced by Taiwan LGBTQ+ community and their underlying causes, and the film’s thematic limitations.